PENGARUH KECEPATAN LAS MIG MATERIAL AA5083H116 PADA LAJU KOROSI DI LINGKUNGAN 3.5% NaCl - -, Mudjijana (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2019)
Transportation equipment of product and people from one island to another using a small or large ship is cheaper than by plane. The ship can be constructed using A36 steel materials and AA5xxx aluminum alloys that are resistant to saline water. The purpose of this research is to investigate the effect of MIG welding speed of AA5083H116 on corrosion rate in a 3.5 wt% NaCl environment. AA5083H116 material of 300mm x 75mm x 3 mm was welded using a MIG Tenjima 200s equipment and using ER5356 electrode of 0.8 mm diameter, at welding speed of 8, 10, 12 mm/s, filler rate of 27 mm/s, and in argon gas environmental. The specimen of 15 mm diameter and 2 mm thick was let to be corroded including the base metal (BM), heat affected zone (HAZ), and weld metal zone. The corrosion testing was carried out at BATAN Serpong using a three-cell potensiodynamic polarization electrode. The results of Tafel plot was showed a corrosion current (icorr) and corrosion voltage (Ecorr), then corrosion rate can be determined. The corroded specimen surfaces were investigated using a scanning electron microscope (SEM) and an energy dispersive spectrometer (EDS). The results of the research show that the corrosion rate of welding speed of 12 mm/s is lower than that of welding speed of 8 mm/s. It is confirmed that the SEM showed that the deterioration of surfaces corrosion is smaller than at HAZ zone.